Carta de Roberto H.Todd a Vicente Balbás - Todd, Roberto H. (My University, 1908)
Documento relacionados con la Liga de municipio.
Keywords: Delgado, Ramón H.; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Municipal government--Puerto Rico.; Gobierno Municipal--Puerto Rico.; Balbás, Vicente, 1864-1926